FAKTOR-FAKTOR YANG MEMPENGARUHI FIRM VALUE PERUSAHAAN SEKTOR CONSUMER NON-CYLICALS YANG GO PUBLIC DI INDONESIA - Fanny Magdalena; Wijaya, Henryanto; Vincent Winaldo; Karen Widjaja; Agus Wahyono (Fakultas Ekonomi dan Bisnis Universitas Satya Negara Indonesia, 2025)
The aim of this research is to analyze the influence of capital structure, firm size and managerial ownership with liquidity as a moderating variable on the Firm Value of consumer non-cylicals companies listed on the Indonesia Stock Exchange (IDX). The sample selection used the purposive sampling method and the population for this study was the 2020-2022 period using 96 data consisting of 32 consumer non-cylicals company samples. The research design used in this study is a descriptive research design. This descriptive research was conducted to understand the existence of one or more variables, by not comparing the variables themselves and looking for a relationship with other variables. In this study, the data processing used the Microsoft Excel 2010 program and the data analysis process used Eviews version 10. This study used a random sample selection technique, namely purposive sampling. This activity was carried out from March to July 2024.